Sustainable Tourism Development: The Case of Barbados - Greenidge, Nathali (2006)
This study examines the issue of sustainable tourism development in the case of Barbados. As part of the background analysis, the study begins by defining what is meant by tourism and discussing its benefits and costs. It then goes on to analyse trends in the tourism industry at both the global and regional level. In this regard, it shows tourism as the largest and fastest growing industry in the world and as being the most important sector for many countries, particularly developing countries. The analysis is then narrowed to Barbados where the evolution and structure of the industry is discussed in detail. Barbados is shown to be heavily dependent on tourism and indeed tourism has become the most significant sector in the economy. It is also identified as the industry that will contribute the most towards the continued economic prosperity for the country and also propel the country into further social development, plus act as a catalyst for the conservation of the physical environment. Therefore, the importance of tourism to the overall development of the country can not be overstated. Yet, tourism can have adverse impacts on the environment and the society if not managed and developed in a manner that is in harmony with the surroundings and the locals. Issues such as management of the islands water resources, over-crowding and the impact on the environment are of paramount importance. Thus, the question arises as to whether the industry is on a sustainable development path or whether its future would require a different approach to the development. The study then reviews the literature on assessing sustainable and applies a number of indicators to the case of Barbados. In general, the results suggest that tourism development in Barbados is on a sustainable path. Specifically, the economic benefits of tourism will continue to accrue to the Barbadian economy well into the long-term, any negative social effects are at manageable levels and the authorities are implementing various measures to deal with the adverse impacts the industry has had on the environment. These measures are aimed at ensuring that the tourism industry develops in harmony with the environment.